The Evaluation of Organizational and Administrative Reality for some University Graduation Parties - Jawad, Sundus Mousa; abdulrasool, Mokhalad dheyaa (International Journal of Psychosocial Rehabilitation, 2020)
Since the graduation took place in the lives of students and professors together and in the light of the high levelreached by the organizational and technical matters as well as this celebration of the meaning of happiness and joyand pride of the students and their families, therefore assigned the graduation ceremony to the sections of studentactivities and the faculties of Physical Education and Sports sciences in Iraqi universities. The results indicate thatall organizational matters and administrative concert graduation fairly equal in importance. Distributed a samplesearch are five levels measured by the organizational and administrative reality, some university graduation parties.Most of the members of the commissions' supreme-court for receptions graduation Students Sample Application wasaverage and above .Some members of the supreme rushed for receptions graduation Students Sample Application wasat an acceptable level and weak .Relying on the scale of the administrative and organizational structure is for thepurpose of measuring the assessment of graduation students of universities.